Problematic aspects of the examination of the quality of care - Yu. Yu. Shvets (Путеводитель предпринимателя)
The article describes the features of examination of quality of medical services (medical care) as a means of control of the quality at the present stage of development of health services in the country. It analysed the regulatory, legal and methodological regulation of health care expertise in Russia and revealed the problematic aspects of its regulation. Abstract interpretation of the concept of «quality», «quality of care», «examination of medical care.» We consider the function of monitoring the quality of care. Identified problematic aspects of organization and the examination of the quality of care at the present stage of development of medicine.